2018
DOI: 10.1002/jor.24040
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric detection of staphylococcal biofilm growth on various prosthetic biomaterials after exposure to daptomycin

Abstract: Primary aim of this in vitro study was to test the efficacy of daptomycin to eradicate staphylococcal biofilms on various orthopedic implant materials. Secondary aim was to quantitatively estimate the formation of staphylococcal biofilm. We tested six clinically important biomaterials: Cobalt chrome, pure titanium, grid-blasted titanium, porous plasma-coated titanium with/without hydroxyapatite, and polyethylene. Biofilms of S. aureus and S. epidermidis were formed on the samples and thereafter exposed to dapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Oga et al found with scanning electron microscopy that S. epidermidis adhered in greater numbers to hydroxyapatite than to the uncoated metals used in this study, 46 and Ravn et al have used microcalorimetry to reach a similar conclusion with S. aureus . 47 In contrast, two other microbiological studies have found that hydroxyapatite is comparatively resistant to staphylococcal adhesion. 27 , 48 Our finding that hydroxyapatite exhibited a similar but slightly increased propensity for biofilm formation with respect to stainless steel mirrors the similar clinical infection rate seen with hydroxyapatite and stainless steel.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Oga et al found with scanning electron microscopy that S. epidermidis adhered in greater numbers to hydroxyapatite than to the uncoated metals used in this study, 46 and Ravn et al have used microcalorimetry to reach a similar conclusion with S. aureus . 47 In contrast, two other microbiological studies have found that hydroxyapatite is comparatively resistant to staphylococcal adhesion. 27 , 48 Our finding that hydroxyapatite exhibited a similar but slightly increased propensity for biofilm formation with respect to stainless steel mirrors the similar clinical infection rate seen with hydroxyapatite and stainless steel.…”
Section: Discussionmentioning
confidence: 93%
“… 45 , 49 The slightly greater viable cell surface density measured on hydroxyapatite in this work is likely to be because, at least in part, of its greater roughness. 47 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…Results from the 72-h experiment must be interpreted with care as the number of specimens is low. However, we do not suspect less variation by increasing the number of Alternative methods for quantification might be measurement of optical density from resolved biofilm on the plates after sonication, or measurement of heat production from dislodged biofilm by microcaloritmetry [15,19].…”
Section: Discussionmentioning
confidence: 94%
“…This is apparent in the ongoing debate concerning sonication [8,29], and sonication findings are not included in the Musculoskeletal Infection Society (MSIS) criteria for periprosthetic infection. First, in vitro studies raise the question whether Staphylococcus epidermidis biofilm might respond to sonication unlike other species [4,5,19]. Second, clinical studies, including refinement with PCR-techniques, show no difference in sensitivity of culture of tissue samples compared to culture of sonication fluid [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…IMC time to detection (TTD, h) was defined as the time between the insertion of the ampoule into the microcalorimeter and the exponentially increasing heat flow production exceeding the threshold of 10 µW [27].The maximum heat flow peak (P max , µW), the time of the maximum heat flow peak (T max , h), and the total heat produced (H tot , J) were defined as the highest value of the heat flow-time curve, the time at which the P max was detected, and the cumulative amount of heat produced during the whole experiment, respectively. IMC data were converted into microbiologically relevant information such as growth rate (µ, J/h) and lag phase (λ, h) by deriving according to growth models, as previously reported [17,22,29,30].…”
Section: Discussionmentioning
confidence: 99%